1996
DOI: 10.1021/ar950031c
|View full text |Cite
|
Sign up to set email alerts
|

Metal [MLx; M = Fe, Cu, Co, Mn]/Hydroperoxide-Induced Activation of Dioxygen for the Oxygenation of Hydrocarbons:  Oxygenated Fenton Chemistry

Abstract: Earlier Accounts have discussed the electrontransfer reduction of dioxygen (O 2 ), 1 the formation and reactivity of superoxide ion (O 2 •-), 2 and the nucleophilic character of hydroxide ion (HO -, Lewis base and one-electron reductant). 3 The first two describe the propensity of nucleophilic O 2 •-to disproportionate via Brønsted acids (HA, including H 2 O) to hydrogen peroxide (HOOH) and O 2 . The one-electron-reductant character of HOthat is discussed in the third led to the discovery of HO --induced redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
180
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(184 citation statements)
references
References 35 publications
4
180
0
Order By: Relevance
“…This demonstrates that FeCl 2 catalyzes the formation of 12, even though it was reported that dialkyl peroxides are unreactive with FeCl 2 . 26 Reaction 1 + (t-BuO) 2 /FeCl 2 f 5 might not involve homolysis, (t-BuO) 2 f 2 t-BuO • . The C-C bond-forming step involves reaction of iminium ions of type 4 with acetylide anions.…”
mentioning
confidence: 99%
“…This demonstrates that FeCl 2 catalyzes the formation of 12, even though it was reported that dialkyl peroxides are unreactive with FeCl 2 . 26 Reaction 1 + (t-BuO) 2 /FeCl 2 f 5 might not involve homolysis, (t-BuO) 2 f 2 t-BuO • . The C-C bond-forming step involves reaction of iminium ions of type 4 with acetylide anions.…”
mentioning
confidence: 99%
“…Oxidized clusters are unstable and degrade, resulting in the release of iron and the inactivation of the enzyme. The released iron is available to react with hydrogen peroxides through the well characterized Fenton reaction (described below) to produce hydroxyl radicals (HO • ), the most toxic of all ROS (11). Hydroxyl radicals indiscriminately oxidize most biomolecules at nearly diffusion-limiting rates.…”
mentioning
confidence: 99%
“…More importantly, the interaction of free Fe(II) with hydrogen peroxide is known to efficiently generate HO • through the Fenton reaction (Eq. 3) (11,14):…”
mentioning
confidence: 99%
“…25,26 Saran et al observed that the hydroxylation of terephthalic acid by hydroxyl radicals, which was generated by iron autoxidation, exhibited a large dependency on pH while that by gamma radiation was markedly less affected by the pH change. 27 Welch et al also observed the different EPR products when comparing the Fenton reaction and iron autoxidation reaction.…”
Section: +mentioning
confidence: 99%